Pembelajaran Diferensiasi untuk Mewujudkan Merdeka Belajar dalam Reformasi Pendidikan di SMAN Umbulsari - Adilla Dhea Sal Sabilla; Novy Eurika; Aulya Nanda Prafitasari (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Educational reform is an effort to increase in the field of education. Ki Hajar Dewantara with the idea that learning must be student-centered. This is in accordance with the kurikulum merdeka that is being implemented in Indonesia in differentiated learning. Differentiated learning is learning that adapts to the needs of each student. With this kurikulum merdeka, it is hoped that education in Indonesia can increase and produce students according to their individual learning interests. However, the application in domestic education units is still not optimal as in Umbulsari High School which is constrained by teachers who still do not understand the concept of differentiated learning and facilities that are still inadequate for differentiated learning. Teachers who do not understand the concept of differentiated learning do not apply this learning so that the currently implemented kurikulum merdeka is not fully used. The application of differentiated learning gets student learning outcomes after being differentiated learning there is an increase. Problems that occur in education units require more frequent outreach from the government and also monitoring the implementation of the kurikulum merdeka by the ministry of education.